Low-temperature phase of hexaguanidinium heptamolybdate monohydrate - Reinoso, Santiago (International Union of Crystallography, 2008)
The crystal structure of the title compound, [C(NH(2))(3)](6)[Mo(7)O(24)]·H(2)O, previously determined at room temperature in the monoclinic space group C2/c from Weissenberg techniques [Don & Weakley (1981 ▶). Acta Cryst. B37, 451–453], has been redetermined from low-temperature single-crystal data in the monoclinic space group P2(1)/c. The asymmetric unit contains one heptamolybdate anion, six guanidinium cations and one water molecule of hydration. The anions and cations are linked by an extensive network of N—H⋯O hydrogen bonds.